Analisis Kesulitan Belajar Bilangan Cacah Kelas 4 SDIT ALMAKA - Amaliyah, Aan; Darmadi, Nodianus; Hikmah Tilova, Martina (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Mathematics is a science that studies how to think by emphasizing the calculation of reason and ratio. In the world of education, mathematics learning has been taught from an early age (Kindergarten or Kindergarten), then continued at the next level of education. Each level of education will be more difficult for the level of reasoning about mathematics. In learning mathematics in elementary school, students often find it difficult to understand, so it is necessary to have a method that must be adjusted to the material and children's abilities to support their ability to achieve learning goals. Numbers are positive integers of {0, 1, 2, 3, 4, 5, .....} and this should have been taught to elementary school students since grade I. This number counting operation includes addition, subtraction, multiplication, and multiplication. Sometimes students often have difficulties in orations in calculating the number of numbers in multiplication. This needs to be analyzed more carefully so that learning can be achieved properly.